2021
DOI: 10.21873/anticanres.14899
|View full text |Cite
|
Sign up to set email alerts
|

The Clinical Utility of Serum CXCR-2 Assessment in Colorectal Cancer (CRC) Patients

Abstract: Background/Aim: The current study aimed to evaluate the clinical utility of the levels of the C-X-C-motif chemokine receptor-2 (CXCR-2) serum receptor in comparison to the carcinoembryonic antigen (CEA) tumor marker and -the C-reactive protein (CRP) inflammatory marker in the diagnosis and prognosis of colorectal cancer (CRC). Materials and Methods: Our study comprised 59 patients with CRC and 46 healthy subjects. Serum concentrations of the analyzed proteins were measured using enzyme-linked immunosorbent ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 33 publications
5
8
0
Order By: Relevance
“…Therefore, in our most recent studies we investigated whether serum CXCL-8 and its specific receptor (CXCR-2) may be used as potential biochemical tumor markers for CRC using the enzyme-linked immunosorbent assays (ELISA) method. We compared the diagnostic utility of serum levels of CXCL-8 and CXCR-2 with classical tumor markers (CEA) for CRC [22][23][24]. Our investigations revealed that serum concentrations of CXCL-8, similar to those of the classical tumor marker, were significantly higher in patients with CRC in comparison to healthy controls-the results are consistent with those obtained by other authors [62].…”
Section: Chemokines and Their Specific Receptorssupporting
confidence: 86%
See 3 more Smart Citations
“…Therefore, in our most recent studies we investigated whether serum CXCL-8 and its specific receptor (CXCR-2) may be used as potential biochemical tumor markers for CRC using the enzyme-linked immunosorbent assays (ELISA) method. We compared the diagnostic utility of serum levels of CXCL-8 and CXCR-2 with classical tumor markers (CEA) for CRC [22][23][24]. Our investigations revealed that serum concentrations of CXCL-8, similar to those of the classical tumor marker, were significantly higher in patients with CRC in comparison to healthy controls-the results are consistent with those obtained by other authors [62].…”
Section: Chemokines and Their Specific Receptorssupporting
confidence: 86%
“…Furthermore, the infiltration of various immune cells, such as tumorinfiltrating leukocytes (TILs), various cytokines and tissue remodeling factors, has also been associated with cancer-related inflammation. Our previous original studies as well as some clinical investigations of other authors prove that selected circulating inflammatory mediators such as cytokines, including chemokines and hematopoietic growth factors (HGFs), specific inflammatory proteins such as C-reactive protein (CRP) and various matrix metalloproteinases, in particular gelatinases (MMP-2, MMP-9) and their tissue inhibitors (TIMP-1, TIMP-2), could be involved in the tumor development, proliferation, migration and angiogenesis of cancer cells (Figure 1), and may be considered potential candidates for novel biochemical markers for CRC (Table 1) [18][19][20][21][22][23][24][25][26][27][28]. Hematopoietic cytokines (HCs), also known as hematopoietic growth factors (HGFs), are small proteins that induce the differentiation and proliferation of hematopoietic progenitor cells.…”
Section: Colorectal Cancermentioning
confidence: 99%
See 2 more Smart Citations
“…Based on our knowledge, the present study is the first to compare the significance of these proteins in relation to the well-established tumor markers (CEA and CA19-9) and the marker of inflammation-C-reactive protein (CRP)-in the diagnosis and progression of GC. Moreover, the present paper is a continuation of our previous research, in which we assessed that serum concentrations of selected chemokines and their specific receptors might be used as potential tumor biomarkers for gastrointestinal malignancies, including pancreatic, esophageal and colorectal cancer [19][20][21][22][23][24][25].…”
Section: Introductionmentioning
confidence: 88%